Cloning, molecular characterization, and spatial and developmental expression analysis of GPR41 and GPR43 genes in New Zealand rabbits. (28th February 2017) - Fu, C. Y.; Liu, L.; Gao, Q.; Sui, X. Y.; Li, F. C.
Abstract : Short-chain fatty acids (SCFAs) play a regulatory role in various physiological processes in mammals and act as endogenous ligands for the G protein-coupled receptors (GPR) 41 and 43. The role of GPR41 and GPR43 in mediating SCFA signaling in the rabbit remains unclear. The present study was to investigate the sequence of the GPR41 and GPR43 messenger RNA (mRNA) and their expression pattern in different tissues and developmental stages in New Zealand rabbit. Comparison of genomic sequences in GenBank using the Basic Local Alignment Search Tool program suggested that the New Zealand rabbit GPR41 mRNA has high similarities with the human (84%), bovine (84%) and Capra hircus (84%) genes. Similarly, GPR43 mRNA has high similarity with the rat (84%) and mouse (84%) genes. Real-time PCR results indicated that GPR41 and GPR43 mRNA were expressed throughout rabbit's whole development and were expressed in several tissues. G protein-coupled receptor 41 and GPR43 mRNA were most highly expressed in pancreas ( P <0.05) and s.c. adipose tissue ( P <0.05), respectively. The expression levels of GPR41 mRNA was down-regulated in duodenum, cecum ( P <0.05) and pancreas and up-regulated in jejunum, ileum, adipose tissue and spleen during growth. G protein-coupled receptor 43GPR43 mRNA was highly expressed in the duodenum, jejunum, ileum, colon, cecum and lung at 15 th day ( P <0.05), whereas the expression levels in the pancreas and spleen increased later after birth, with the highest expression at 60 th day ( P <0.05).